2009
DOI: 10.1039/b902361e
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(III) complexes bearing 2-benzazole-1,10-phenanthrolines: synthesis, molecular structures and ethylene oligomerization and polymerization

Abstract: The 2-benzazole-1,10-phenanthrolines and their chromium(III) complexes were synthesized and characterized by elemental and spectroscopic analyses as well as by single-crystal X-ray crystallography. X-Ray crystallographic analyses of C6 and C8 reveal an octahedral geometry around both chromium centers. The electronic spectra of the chromium complexes exhibit d-d transitions typically of a pseudo-octahedral coordinated d(3) ion, falling into the region nu(1)(4)A(2g)-->(4)T(2g) 600-700 nm,nu(2)(4)A(2g)-->(4)T(1g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 65 publications
3
33
1
Order By: Relevance
“…Chart 5.3 summarizes the complex with the tridentate ligand, 3a [64], 3b [65], 3c [66], 3d [67][68][69], and 3e [70] (Table 5.1 run 24). Most of the complexes afford oligomers with SchulzFlory distribution.…”
Section: General Aspectmentioning
confidence: 99%
“…Chart 5.3 summarizes the complex with the tridentate ligand, 3a [64], 3b [65], 3c [66], 3d [67][68][69], and 3e [70] (Table 5.1 run 24). Most of the complexes afford oligomers with SchulzFlory distribution.…”
Section: General Aspectmentioning
confidence: 99%
“…The ligand 1 was prepared according to a published procedure [9]. Cis,cis-1,3,5-cyclohexanetricarboxylic acid, diphenylphosphoryl azide(DPPA) and Cr(acac) 3 were purchased from Sigma-Aldrich(Pennsylvania, USA) and used as received. Polymerization grade ethylene was obtained from Daqing Petro-Chemical Ltd. (Daqing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years there has been a substantial acceleration in research activity concerned with homogeneous transition metal catalysts for ethylene oligomerization and polymerization. Chromium catalysts play an important role in both of these processes [1][2][3][4][5][6][7][8]. Since the first report of ethylene tetramerization to form 1-octene using Cr-bis(diphenylphosphino)amine (PNP) catalysts [9], numerous studies have investigated the relationship between ligand structure and catalytic properties.…”
mentioning
confidence: 99%
“…In order to investigate this kind of catalyst in detail, Zhang and co-workers did research and reported their investigation on bis(benzimidazolyl)pyridine ligands [22]. They prepared a series of these ligands (Fig.…”
Section: Nnn Ligandsmentioning
confidence: 99%
“…Chromium complexes bearing NNN ligands exhibited high catalytic activities in ethylene oligomerization and polymerization [15,21,22]. It is reported that chromium complexes ligated by NNN species such as bis(imino)pyridine, (2-pyridylmethyl)amines, β-diketimate and pyrrolide-imine ligands can polymerize or oligomerize ethylene with great activity [21,[23][24][25].…”
Section: Nnn Ligandsmentioning
confidence: 99%